Steam gasification of wood biomass in a fluidized biocatalytic system bed gasifier: A model development and validation using experiment and Boubaker Polynomials Expansion Scheme BPES - Vecchione, Luigi; Moneti, Marta; Di Carlo, Andrea; Savuto, Elisa; Pallozzi, Vanessa; Carlini, Maurizio; Boubaker, Karem; Longo, Leonardo; Colantoni, Andrea (Center of Biomass & Renewable Energy, Diponegoro University, 2015)
One of the most important issues in biomass biocatalytic gasification is the correct prediction of gasification products, with particular attention to the Topping Atmosphere Residues (TARs). In this work, performedwithin the European 7FP UNIfHY project, we develops and validate experimentally a model which is able of predicting the outputs,including TARs, of a steam-fluidized bed biomass gasifier. Pine wood was chosen as biomass feedstock: the products obtained in pyrolysis tests are the relevant model input. Hydrodynamics and chemical properties of the reacting system are considered: the hydrodynamic approach is based on the two phase theory of fluidization, meanwhile the chemical model is based on the kinetic equations for the heterogeneous and homogenous reactions. The derived differentials equations for the gasifier at steady state were implemented MATLAB. Solution was consecutively carried out using the Boubaker Polynomials Expansion Scheme by varying steam/biomass ratio (0.5-1) and operating temperature (750-850Â°C).The comparison between models and experimental results showed that the model is able of predicting gas mole fractions and production rate including most of the representative TARs compounds